2022
DOI: 10.1155/2022/1782221
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Markers to Detect Nonalcoholic Fatty Liver Disease in a Male Hispanic Population

Abstract: Background. Nonalcoholic fatty liver disease (NAFLD) is one of the leading causes of chronic liver disease and is closely associated with cardiometabolic disorders, being insulin resistance (IR) the common pathogenic mechanism. The triglycerides/glucose (TyG) index and triglycerides/HDL-c (TG/HDL) ratio are markers correlated with IR. We compared the capacity of these two indexes, alongside IR, to detect NAFLD. Methods. In a cross-sectional cohort study, we examined 263 active military personnel from the Colom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…In general, our results are consistent with previous studies regarding the association between the TG/HDL-C ratio and NAFLD. Our present study indicated that subjects with hepatic steatosis had significantly higher TG/HDL-C ratio values than those without hepatic steatosis, comparable to the results of prior studies [10], [16]- [19]. The TG/HDL-C ratio is independently correlated with NAFLD, according to two large cross-sectional studies [16], [17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, our results are consistent with previous studies regarding the association between the TG/HDL-C ratio and NAFLD. Our present study indicated that subjects with hepatic steatosis had significantly higher TG/HDL-C ratio values than those without hepatic steatosis, comparable to the results of prior studies [10], [16]- [19]. The TG/HDL-C ratio is independently correlated with NAFLD, according to two large cross-sectional studies [16], [17].…”
Section: Discussionsupporting
confidence: 91%
“…Another cohort study also reported an independent association between the TG/HDL-C ratio and NAFLD in non-obese subjects [18]. The TG/HDL-C ratio is also effective in detecting NAFLD, as reported by Fan et al [17], Chen et al [18], and and Pérez-Mayorga et al [19], with cut-off values ranging from 0.64 to 3.83, probably related to ethnic differences. However, most of those studies involved apparently healthy individuals who were not diabetic, except for the study by Li et al [10], which involved newly diagnosed T2DM patients.…”
Section: Discussionmentioning
confidence: 64%